محاسبة شركات التأمين - أحلام, داودي; سمية, حمزة; دليلة, قسومي (جامعة الوادي - University of Eloued, 2023)
محاسبة شركات التأمين هي عملية تحليل وتقييم الأنشطة المالية لشركات التأمين وإعداد التقارير والميزانيات المالية لها. تتمثل أهمية هذه العملية في تقديم معلومات دقيقة عن النتائج المالية للشركة ومدى نجاحها في تحقيق الأهداف المالية المحددة. تشمل مهامها حساب الأرباح والخسائر، إعداد التقارير المالية، إدارة الضرائب، ومراقبة أنظمة المحاسبة والتقارير. كما يتطلب عمل محاسبة شركات التأمين الإلمام بالتشريعات واللوائح المتعلقة بالتأمين والمحاسبة والضرائب، وبالنظم المحاسبية الدولية. Holding insurers accountable is the process of analyzing and evaluating insurers' financial activities and preparing their financial reports and budgets. The importance of this process is to provide accurate information on the financial results of the Company and the extent to which it succeeds in meeting the financial targets set. Its tasks include profit and loss accounting, financial reporting, tax administration, and monitoring of accounting and reporting systems. Accounting for insurance companies also requires familiarity with insurance, accounting and tax legislation and regulations, and with international accounting systems.
Keywords: محاسبة، شركات التأمين، التقارير المالية،; Accounting,Insurance companies,Financial reports